ANALISIS EKONOMI MAKRO DAN PENGARUHNYA TERHADAP KEMISKINAN (STUDI PADA PEMERINTAH KABUPATEN TAPANULI SELATAN) - Ali Hardana; Nurhalimah, Nurhalimah; Sulaiman Efendi (Universitas 45 Surabaya, 2022)
Poverty is a multidimensional problem so that it can be viewed from various points of view. This study aims to analyze the influence of Macroeconomic Conditions which include: Population Growth, Unemployment Rate, Education Level, Inflation Rate, Minimum Wage and Economic Growth on poverty in South Tapanuli Regency. This research is a quantitative study using secondary data and primary data. time series from the Central Bureau of Statistics and primary data from research respondents. Secondary data was obtained from the Central Bureau of Statistics and Primary data was obtained from respondents. Data were collected using methods: Observation, Interview, Documentation and Questionnaires. Using regression analysis shows that: Population Growth, Unemployment Rate, Education Level, Inflation Rate, Minimum Wage and Economic Growth affect poverty in South Tapanuli District, But the Minimum Wage has no effect.